Antibody Panel Based N-glycan Imaging for N-Glycoprotein Biomarker Discovery - Black, Alyson P. (Curr Protoc Protein Sci, 2019)
Antibody Panel Based N-glycan imaging is a novel platform for N-glycan analysis of immunocaptured proteins. N-glycosylation is a post-translational modification of pathophysiological importance and is often studied in the context of disease biomarkers. Determination of protein-specific N-glycosylation changes in patient samples has traditionally been laborious or limited to study of a single protein per analysis. This novel technique allows for the multiplexed analysis of N-glycoproteins from biofluids. Briefly, this platform consists of antibodies spotted in an array panel to a microscope slide, specific capture of glycoproteins from a biological sample, and then enzymatic release of N-glycans for analysis by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS). N-glycans are detected at each individual spot, allowing N-glycan information to easily be linked back to its protein carrier. Using this protocol, multiplexed analysis of N-glycosylation on serum glycoproteins can be performed. Human serum is discussed here, but this method has potential to be applied to other biofluids and to any glycoprotein that can be captured by a validated antibody. Basic Protocol 1: Antibody Panel Based N-glycan Imaging by MALDI MS